Character Education In The Digital Era; Building Students Religious Values In The Midst Of Technological Disruption At Junior High School 1 Bayan - Raden Sumiadi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The massive digital transformation that has occurred has brought significant changes to the world of education, including in terms of character formation of students. This research aims to describe the strategy and implementation of character education in building students' religious values at SMPN 1 Bayan amidst technological disruption. This research uses a descriptive qualitative approach where data is collected through observation, in-depth interviews and documentation studies. Informants consisted of school principals, Islamic religious education teachers, homeroom teachers, and students. The research results show that schools implement a number of strategies, including familiarizing themselves with religious activities, integrating religious values in learning, and using digital media as a means of character education. The main challenges faced include the negative influence of digital content and limited control over students' use of technology. However, collaboration between the school, parents and community is a key factor in maintaining and developing religious values among students. This research certainly recommends strengthening the role of teachers and innovation in value-based learning as an adaptive response to the digital era.